Social Networks and Collective Action Decisions Facing the Post-COVID-19 Situation in Pujon Kidul Village, Indonesia - Permana, Mirza; Arifin, Muhammad Asfihan Nur; Aledeh, Muhammad; Rahmawati; Rachman, Cyril Bernard; Pamungkas, Yan Akbar (Journal of Regional and Rural Studies, 2025)
Pujon Kidul Village, located in Malang Regency, Indonesia, is a prominent tourist destination recognized for effectively leveraging its local tourism potential. However, during the COVID-19 pandemic, the village faced significant declines in tourist numbers, severely impacting its economy. In crisis situations, the involvement of local communities becomes critical for resilience and recovery. Specifically, in the post-pandemic period, community participation has emerged as essential for sustainable tourism revitalization. This study investigates the influence of social networks on collective decision-making in Pujon Kidul Village, Indonesia, and their contribution to sustainable tourism recovery following the COVID-19 pandemic. Data were collected from 225 households using Harry King's Nomogram sampling method, ensuring a representative sample. The research employed Structural Equation Modeling - Partial Least Squares (SEM-PLS) to analyze the relationship between community social networks and collective decision-making. The findings reveal a strong positive correlation between social networks and effective collective action, highlighting the essential role of communication, collaboration, and coordinated efforts in driving post-pandemic tourism recovery. The results emphasize that robust social networks are crucial for enhancing resilience and fostering sustainable tourism development in crisis-affected communities.